Tribological evaluation of electric vehicle driveline lubricants in an electrified environment - Lee, Peter M.; Sanchez, Carlos; Frazier, Cole; Velasquez, Andrew; Kostan, Travis (Frontiers in Mechanical Engineering, 2023)
Electrification continues to permeate the automotive industry, with future projections showing an exponential growth in the market share for both light and heavy-duty applications. Existing test methods for automotive applications were developed to model internal combustion engine vehicles and drivelines and are not appropriate for electric drivelines that experience stray electric currents. Tribometers can be used to evaluate friction and wear on modeled surfaces simulating in-vehicle operation. In this work, a commercially available tribometer was modified to isolate an electrical input into a tribological contact. After necessary modifications to the tribometer, a test matrix was completed for investigating different temperatures, load conditions, speed conditions, voltage input types, frequencies of AC signal, and shapes of AC signal. These parameters were tested on three lubricants—two typical automatic transmission fluid formulations and gear oil used in differential applications. Friction was measured throughout the tests, and wear scar width was measured at the end of each test. Results indicated that temperature, DC voltage, AC frequency, lubricant, and test profile had statistically significant differences in wear scar width. For electrical parameters, AC frequency produced different results from DC voltage when no voltage was applied. This significance applied to only one lubricant, with the other two lubricants having mixed results.